2020
DOI: 10.1101/2020.06.25.172379
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

POMC-specific knockdown of Tril reduces body adiposity and increases hypothalamic leptin responsiveness

Abstract: In a public dataset of transcripts differentially expressed in selected neuronal subpopulations of the arcuate nucleus, we identified TLR4-interactor with leucine-rich repeats (Tril) as a potential candidate for mediating the harmful effects of a high-fat diet in proopiomelanocortin (POMC) neurons. The non-cell-specific inhibition of Tril in the arcuate nucleus resulted in reduced hypothalamic inflammation, protection against diet-induced obesity associated with increased whole-body energy expenditure and incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Studies also showed that the glial cells are particularly affected by saturated fatty acids (SFAs) diet due to heterogeneity and neurogenic neuroinflammation during degenerative conditions [41]. More significantly, neonatal high-fat diet feeding seems to raise plasma glucose levels associated with microglial activation in the hypothalamus in weeks [42,43]. Indeed, reactive morphological and functional changes that characterized microglia activation increase inflammatory cytokines, nitric oxide, and reactive oxygen species (ROS).…”
Section: Data Collectionmentioning
confidence: 99%
“…Studies also showed that the glial cells are particularly affected by saturated fatty acids (SFAs) diet due to heterogeneity and neurogenic neuroinflammation during degenerative conditions [41]. More significantly, neonatal high-fat diet feeding seems to raise plasma glucose levels associated with microglial activation in the hypothalamus in weeks [42,43]. Indeed, reactive morphological and functional changes that characterized microglia activation increase inflammatory cytokines, nitric oxide, and reactive oxygen species (ROS).…”
Section: Data Collectionmentioning
confidence: 99%